The Image of Woman in Pre-Islamic Qasida: The Mu’allaqat Poetry as a Case Study. - Kamaldeen, Yakubu Zahrrah (AUC Knowledge Fountain, 2012)
This study is intended to examine the depiction of woman in the pre-Islamic poetic collection known as the Mu'allaqat; which are considered the best piece of poetic collection in literary Arabic. The significance of this study is to identify the true rationale behind the poets' over emphasis on woman in their odes. A combination of both empirical and library-based method is adopted in this study and Discourse and Qualitative contents Analysis are the techniques applied in interpreting the data. The study identifies two different types of women in the odes, the ideal woman who is not a specific woman per se, but a woman considered a deity and worshiped due to her fertility and reproductive function as a mother, she was deified by invoking her memory in the prelude of the poems as form of reverence and incantations which the poets inherited from the ancient religious legend and standardized it as format for starting a Qasida. The other type of woman is the real normal woman, whom most of the time is a true beloved of the poet, who the poet describes in his poem by giving a vivid account for their love affairs. She may also be a bar attendant, and Jaariya or slave woman. The study found the depiction of both the Ideal and real woman in Mu'allaqat to confine to descriptions and similes them to objects found in the surroundings of the poets. She is therefore compared to wild deserts animals and birds and from such descriptions it is deduced women were always given priority in moments of insecurity and drought, they command a maximum freedom in choosing their partners and had absolute rights to revoke marital relationship with their male partners without any hindrance or obstacle. Above all, she also participates in the warfare by nursing the injured, the horses as well as feeding them.